Glyphosate in agronomic performance and seed quality of soybean with cp4-EPSPs and cry1ac genes - Silva, André Felipe Moreira; Albrecht, Alfredo Junior Paiola; Albrecht, Leandro Paiola; Pellicci, Victor Aparecido; Giovanelli, Bruno Flaibam [UNESP]; Ghirardello, Giovani Apolari; Viana, Henrique Rodrigues Milagres; Filho, Ricardo Victoria (Polish Academy of Sciences Chancellery, 2018)
The second generation of glyphosate-tolerant soybean (GT2 soybean) was developed through a different technique of insertion of the glyphosate-insensitive EPSPs gene, in comparison with first generation of glyphosate-tolerant soybean. However, there is not enough information available about glyphosate selectivity in GT2 soybean and the effects on the quality of seeds produced. The aim of this study was to evaluate tolerance to glyphosate and seed quality of soybean cultivar NS 6700 IPRO (GT2) with cp4-EPSPs and crylAc genes, after application at post-emergence (V4). The experiment was conducted in a randomized block design with four replicates and seven treatments, or rates of glyphosate (0; 720; 1,440; 2,160; 2,880; 3,600; 4,320 g of acid equivalent - a.e. • ha -1 )- Assessments were performed for crop injury, SPAD index and variables related to agronomic performance and seed quality. A complementary trial with the same cultivar and treatments in a greenhouse was conducted in a completely randomized design with four replications. Data analysis indicated no significant effect of glyphosate on V4 on agronomic performance and physiological quality of seeds, for two growing seasons. The soybean cultivar NS 6700 IPRO (GT2), with cp4-EPSPs and crylAc genes, was tolerant to glyphosate up to the maximum rate applied (4,320 g a.e. • ha -1 ) at post-emergence (V4). The quality of soybean seeds was not affected by glyphosate up to the maximum rate applied (4,320 g a.e. • ha -1 ) at post-emergence (V4).
Keywords: Crop injury; Glycine max; Glyphosate-tolerant soybean; Herbicide; Selectivity